2020
DOI: 10.22541/au.160157569.93781826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of severity and mortality of COVID-19 at a tertiary care center in a Lower-middle income country

Abstract: Objective COVID-19 mortality and outcomes differ significantly across the globe. Limited data exists from low-middle income countries (LMICs) on risk-factors for COVID-19 severity and mortality. We describe the clinical spectrum and predictors of mortality and severity of illness in COVID-19 from a single center in Karachi, Pakistan. Methods Retrospective cohort study of adults admitted with COVID-19 between February-June 2020 were reviewed and logistic regression applied on admission related risk-factors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…ICU admission was needed for 59% (95/160). Approximately, 38.8% (66/170) required mechanical ventilation (MV) hence our patient population appears to be sicker compared to the only other unpublished data from the city[10].…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…ICU admission was needed for 59% (95/160). Approximately, 38.8% (66/170) required mechanical ventilation (MV) hence our patient population appears to be sicker compared to the only other unpublished data from the city[10].…”
mentioning
confidence: 80%
“…ICU admission was needed for 59% (95/160). Approximately, 38.8% (66/170) required mechanical ventilation (MV) hence our patient population appears to be sicker compared to the only other unpublished data from the city [ 10 ]. We believe, being a private referral center they may have admitted milder spectrum patients for the purpose of isolation and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient population appears to be sicker compared to the only other unpublished data from the city. The reason for this difference could be admission of non-critical patients for monitoring and isolation since it was a private hospital [6] On the contrary, as mentioned before, our center is a philanthropic, free of cost referral centre for the underprivileged with limited bed capacity. Hence, admission was strictly reserved for critical patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Goujon suggested that the observed gender differences point at the need to pay special attention to health care workers -regardless whether they are male or female [15]. Other studies consistent with this were [16][17][18][19].…”
Section: Discussionmentioning
confidence: 96%